PERAN PDHI (PERSAUDARAAN DJAMAAH HAJI INDONESIA) DALAM MENGEMBANGKAN PERADABAN MASYARAKAT (ANALISA MANAJEMEN SUMBER DAYA MANUSIA) - Aris Risdiana (Jurnal MD, 2015)
PDHI an organization that helped organize the pilgrims to carry outcommunity service in the form of social activity. The successful implementationof the program of planned activities is dependent upon the management ofhuman resources. The purpose of this study was to describe the managementof human resources in PDHI as a major asset and supporter of the successof social programs that have been implemented. This research is descriptivequalitative, where data collection is done through observation, interviewswith speakers and documentation. Subjects were PDHI board, while theobject of study is the social activities carried out by PDHI. In this study, thevalidity of the data was tested by using the technique of triangulation. Resultsillustrate that PDHI quite actively participated in developing civilization,although the management of human resources in it is still relatively simple.PDHI has initiated the construction of mosques in various regions inYogyakarta, Central Java, East Java, Bali, NTB and establish educationalinstitutions, hospitals, Islamic centers and orphanages. This study provides theconclusion that the management of human resources in PDHI still simple,human resource management has been implemented but not conceptualizedby default and only implicitly applied.Keywords: human resource management, social activities.